Impact of Nurse Residency Programs on Retention and Job Satisfaction: An Integrative Review - McGregor, Heather M.; Scott, Morgan; Gorham, Robyn; Hunt, Elena (European Scientific Journal, ESJ, 2024)
Retention of new nurses is vital within the context of the nursing shortage Canada is currently facing. Nurse residency programs need to be explored to better understand their role in combating the nursing shortage. The study utilized Whittemore and Knafl’s integrative review methodology to review current literature on nurse residency programs in The United States of America and focuses on retention rates, job satisfaction and intent to leave as a means for understanding the role of nursing residency programs within the Canadian nursing context. The literature review found that Nurse Residency Programs (NRP) can improve retention and job satisfaction for newly licensed registered nurses (NLRNs), but their impact on reducing turnover intention is unclear and needs further study.